A Novel Classification Method for Syndrome Differentiation of Patients with AIDS. (9th June 2015) - Zhao, Yufeng; He, Liyun; Xie, Qi; Li, Guozheng; Liu, Baoyan; Wang, Jian; Zhang, Xiaoping; Zhang, Xiang; Luo, Lin; Li, Kun; Jing, Xianghong
Abstract : We consider the analysis of an AIDS dataset where each patient is characterized by a list of symptoms and is labeled with one or more TCM syndromes. The task is to build a classifier that maps symptoms to TCM syndromes. We use the minimum reference set-based multiple instance learning (MRS-MIL) method. The method identifies a list of representative symptoms for each syndrome and builds a Gaussian mixture model based on them. The models for all syndromes are then used for classification via Bayes rule. By relying on a subset of key symptoms for classification, MRS-MIL can produce reliable and high quality classification rules even on datasets with small sample size. On the AIDS dataset, it achieves average precision and recall 0.7736 and 0.7111, respectively. Those are superior to results achieved by alternative methods.